Diffuse Involvement of Aorta in Patient with Familial Hyperlipidemia. (3rd April 2011) - Can, Mehmet Mustafa; Tanboga, Ibrahim Halil; Akgun, Taylan
Abstract : Familial hyperlipidemia (FH) is an inherited metabolic disorder caused by low-density lipoprotein (LDL) receptor abnormality. The delayed clearance of serum LDL results in severe hypercholesterolemia, which leads to the accumulation of LDL-derived cholesterol in skin, tendons, and arterial walls.In homozygous form of the disease, severely atheromatous involvement of the aorta extending to the coronary ostia is almost always present, and particular surgical strategy is required to prevent atheroembolic events.